2000
DOI: 10.1074/jbc.m000202200
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylases Specifically Down-regulate p53-dependent Gene Activation

Abstract: p53, the most commonly mutated gene in cancer cells, directs cell cycle arrest or induces programmed cell death (apoptosis) in response to stress. It has been demonstrated that p53 activity is up-regulated in part by posttranslational acetylation. In agreement with these observations, here we show that mammalian histone deacetylase (HDAC)-1, -2, and -3 are all capable of downregulating p53 function. Down-regulation of p53 activity by HDACs is HDAC dosage-dependent, requires the deacetylase activity of HDACs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
303
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(315 citation statements)
references
References 48 publications
10
303
1
1
Order By: Relevance
“…This dependence appears to vary with the agent used and may be due to differences in potency. Furthermore, acetylation of p53 occurs following HDAC inhibitor administration and may increase its activity and reduce targeting of p53 for degradation [22,39,40]. However, others have shown HDAC inhibitors to have apoptotic effects independent from p53 [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dependence appears to vary with the agent used and may be due to differences in potency. Furthermore, acetylation of p53 occurs following HDAC inhibitor administration and may increase its activity and reduce targeting of p53 for degradation [22,39,40]. However, others have shown HDAC inhibitors to have apoptotic effects independent from p53 [41].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these effects were originally thought to be due to hyperacetylation of histones and activation of previously silenced genes. However, it appears that these agents cause hyperacetylation of a variety of proteins, the subject of recent studies [22,23]. It has been suggested that the tumor specificity of these agents is related to their ability to induce apoptosis [24].…”
Section: Introductionmentioning
confidence: 99%
“…The p53 gene is negatively regulated by HDACs and the protein is a known substrate for HATs and HDACs (Sakaguchi et al, 1998;Luo et al, 2000). Indeed, in response to DNA damage p53 is acetylated at lysine residues in the C-terminal region by the HATs, p300 and PCAF which is thoughtalong with phosphorylation -to stabilize the molecule and it is accumulated in the nucleus where it regulates transcription (Sakaguchi et al, 1998;Juan et al, 2000;Luo et al, 2000). Among numerous other functions, activated p53 induces transcription of a series of proapoptotic Bcl-2 family members (Oda et al, 2000;Nakano and Vousden, 2001).…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 99%
“…1,2 Histone deacetylases (HDAC) represent the family of enzymes involved in dynamic regulation of chromatin structure during transcription, but can also deacetylate a number of non-histone substrates. [3][4][5][6][7][8][9] A growing body of evidence implicates HDAC as playing an important role in carcinogenesis, particularly, in colorectal cancer, as suggested by expression profiling of colon cancer cells treated by HDAC inhibitor trichostatin A. [3][4][5] Histone deacetylases may be involved in carcinogenesis in different ways.…”
mentioning
confidence: 99%
“…Class I HDAC may downregulate tumor suppressors such as p53 and von Hippel-Lindau (VHL) gene product. [6][7][8] HDAC1 may also affect cancer progression by inhibiting estrogen receptor alpha (ER-a) protein expression and its transcriptional activity. 9 Recent experiments with siRNA for Class I and Class II HDAC demonstrated that the former (particularly HDAC1 and HDAC3) are implicated in regulation of proliferation and survival of cancer cells.…”
mentioning
confidence: 99%